Patient characteristics and resource utilisation in paediatric intensive care. - Gemke, R J (1994)
To determine the relation between basic clinical characteristics and resource utilisation in paediatric intensive care, an open prospective study was performed. Resource utilisation was expressed using the therapeutic intervention score system (TISS) and length of stay (LOS), from which total resource utilisation per admission (TISSTOT) and average daily resource utilisation (TISSMEAN = TISSTOT/LOS) were obtained. Overall 593 admissions, totalling 3130 days, were included. Mortality was 8.4% and non-survivors accounted for 14.1% of overall resource utilisation. In non-survivors, TISSTOT and TISSMEAN were higher, whereas LOS was not different from survivors'. Severity of illness, surgical status, significant chronic comorbidity, emergency admission, and transfer status constituted the major predictive determinants of TISSTOT (r2 = 0.19) and TISSMEAN (r2 = 0.45) in multiple regression analysis. High resource utilisation in high risk patients was probably warranted, as effectiveness of prolonged intensive treatment was demonstrated. It is concluded that TISSTOT and TISSMEAN are appropriate, non-monetary measures of resource utilisation, a considerable proportion of which are determined by a concise set of basic clinical characteristics.